Acclimatization of microbial community of submerged membrane bioreactor treating hospital wastewater. (January 2021) - Tiwari, Bhagyashree; Sellamuthu, Balasubramanian; Piché-Choquette, Sarah; Drogui, Patrick; Tyagi, Rajeshwar D.; Vaudreuil, Marc Antoine; Sauvé, Sébastien; Buelna, Gerardo; Dubé, Rino
Highlights: The microbiome of SMBR during acclimatization with HWW was investigated. Pathogenic bacteria were abundant in phase 3 of acclimatization. Shift in the micro-eukaryotes community at phase 3 of acclimatization was observed. Abstract: This study was performed to understand the dynamics of the microbial community of submerged membrane bioreactor during the acclimatization process to treat the hospital wastewater. In this regard, three acclimatization phases were examined using a mixture of synthetic wastewater (SWW) and real hospital wastewater (HWW) in the following proportions; In Phase 1: 75:25 v/v (SWW: HWW); Phase 2: 50:50 v/v (SWW: HWW); and Phase 3: 25:75 v/v (SWW: HWW) of wastewater. The microbial community was analyzed using Illumina high throughput sequencing to identify the bacterial and micro-eukaryotes community in SMBR. The acclimatization study clearly demonstrated that shift in microbial community composition with time. The dominance of pathogenic and degrading bacterial communities such as Mycobacterium, Pseudomonas, and Zoogloea was observed at the phase 3 of acclimatization. This study witnessed the major shift in the micro-eukaryotes community, and the proliferation of fungi Basidiomycota was observed in phase 3 of acclimatization.